Effect of long-term intense swimming training on the upper body peak oxygen uptake of prepubertal girls - Obert, P.; Courteix, D.; Lecoq, A. M.; Guenon, P. (European Journal of Applied Physiology, 1996)
The purpose of the present investigation was to determine the effect of a long-term intense swimming programme on the aerobic potential of prepubertal girls. Five girls [GS, aged 9.3 (SD 0.5) years] participated in a 40-month intense training period. The girls trained on average 10-12 h*week(-1), approximately 1 h-1.5 h twice a day, 5 days each week. Nine girls [CG aged 9.3 (SD 0.4) years] who were engaged in various activities (on average 1-4 h*week(-1)), but not in sports involving upper body muscle mass, served as the control group. All the children completed, on a special swim bench, an incremental maximal exercise prior to (pretest) and after (post-test) the swimming programme. Biometric parameters and the peak oxygen uptake (VO(2peak)) were determined using the same procedure at the pre- and post-test sessions. There was no significant difference between the two groups for any of the variables at the beginning of the study. The biometric characteristics remained similar at the post-test session, indicating that intense swimming training early in life has no influence on the physical growth of prepubertal children. The VO(2peak) expressed in absolute values, however, increased over a year in GS and CG by 38 percent and 13 percent, respectively. The improvement in CG VO(2peak) was related to normal growth and development while that of GS was much higher (P<0.01) than would have been expected due to growth factors alone. The reason for such an improvement could be attributed to an increase in the stroke volume and/or in the difference of the arteriovenous concentration of oxygen since the maximal O(2) pulse was different between CG and GS only at the post-test. Moreover, it increased after 10 months only in GS (delta maximal O(2) pulse: GS 1.09, P<0.01; CG 0.27 NS, ml.beat(-1)). Thus, the results of this study show that physiological adaptations can occur in prepubertal children as a consequence of intense physical training.